Range ecology at disequilibrium - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Range ecology at disequilibrium edited by Roy Behnke Jr lan Scoones and Carol Kerven 1993 248pp